ASSESSMENT OF PROJECT-BASED LEARNING IN SCIENCE CLASS - Noni Agustina (LP2M-PMP Universitas Siliwangi, 2016)
This study reports the students’ assessment through applying the project-based learning in science class for elementary school. The research methodology applied is case study with qualitative approach. The participants of this study are teacher and students of grade 1 and 5 at Budi Luhur elementary school. The instruments to collect data are classroom observation sheets, interviews and rubric of project-based assessment for science class. The result shows that project-based learning is conducted in semester 2 as the substitution of written mid-term test. It is non-test because project-based learning emphasizes on the authentic learning, therefore it is applicable and meaningful for the students. The steps undertaken in project-based learning consist of planning, implementation and evaluation. The assessment of project-based learning uses analytical rubric comprising four scales, 4 (excellent), 3 (good), 2 (fair), dan 1 (poor). To conclude, the project-based learning makes the students glad and enthusiastic. It also encourages the students to have higher cognitive thinking (synthesizing level in Bloom’s taxonomy) and build students’ character.Kata Kunci : assessment, project-based learning, rubric.